(untitled) (Journal of Educational Sciences, 2019)
Currently, high sports results can be achieved only when the training process will be carried out on a scientific basis. Records and generally high achievements in sport are impossible without maximum abilities and optimum preparedness of athletes for competitions. As in any other sport, in rowing and canoeing to show high sports results a great role is played by the optimal pre-start readiness of the rowers. The problem is that rowing researchers, in particular, rowing and canoeing, do not pay enough attention in training qualified rowers to their pre-start conditions, and if they do, they are mainly from a psychological point of view, using the method of psychological influence. However, not all athletes are equally amenable to psychological suggestions (influences). In this regard, the authors set a research goal: to develop and substantiate the positive impact of special physical exercises to optimize the pre-launch readiness of qualified rowers in kayaks and canoes. Thus, the article presents a scientific justification for the use of physical exercises, tested in a natural pedagogical experiment and positively influenced the athletic performance of qualified rowers in kayaks and canoes. Key words: optimization, prestarting conditions, special physical exercises, qualified rowers in kayaks and canoes.